Basic Materials Used in Removable Orthodontic Constructions in Children (Progress Annals: Journal of Progressive Research, 2023)
The rapid development of modern orthodontic technology has led to the widespread introduction of previously unused structures of orthodontic devices made of various groups of restorative materials